Estimating and preventing hospital internal turnover of newly licensed nurses: A panel survey. (August 2016) - Kovner, Christine T.; Djukic, Maja; Fatehi, Faridaben K.; Fletcher, Jason; Jun, Jin; Brewer, Carol; Chacko, Thomas
Abstract: Background: Registered nurse job turnover is an ongoing problem in the USA resulting in significant financial costs to both organizations and society. Most research has focused on organizational turnover with few studies about internal or unit-level turnover. Turnover of new nurses in hospitals has particular importance as almost 80% of new nurses work in hospitals and have higher turnover rates when compared to experienced nurses. This paper focuses on new nurses' unit-level turnover rates in hospitals. Objectives: The purpose of this study is to: (1) identify factors that predict new nurses staying in the same units, positions, and job titles to inform unit-level retention strategies, and (2) examine the changes in work environment perceptions over time between nurses who remain in the same unit, position, and title to those who changed unit, position and/or title. Study design: A panel survey design was used to analyze changes over time. Participants: Participants were newly licensed registered nurses who were licensed for the first time between August 1st, 2004 and July 31st, 2005. The nurses came from metropolitan statistical areas or rural areas that were nested to reflect a nationally representative USA sample (58% response rate). The analytic sample for this study was 1335. Data sources: Data were collected in January 2006 and 2007 following the Dillman total design approach. All potential respondents received paper surveys and non-responders received repeated mailings. Results: Using multinomial regression the five variables with the largest effects on unit retention were (1) variety (positive), (2) having another job for pay (negative), (3) first basic degree (having a bachelors or higher degree increased the probability of staying), (4) negative affectivity (positive), and (5) job satisfaction (positive). Nurses who changed unit, and/or position, and/or title reported more positive change scores on a variety of work attitudes. Discussion: Almost 30% of new nurses working in hospitals leave their unit, and/or position, and/or title during their first year of work. Our results point to the variables on which managers can focus to improve unit-level retention of new nurses. Although participants were from a nationally representative sample of nurses who were newly licensed in 2004–2005, with the geographical shifts in the USA population in the last 10 years the sample may not be geographically representative of new nurses who graduated in 2015.